Error rates associated with the use of recently proposed breakpoints for testing Pseudomonas aeruginosa versus gentamicin, tobramycin, and amikacin by the standardized disk agar diffusion test. - Woolfrey, B F (1983)
Two hundred fifteen Pseudomonas aeruginosa isolates were tested in parallel by the disk agar diffusion test, using a standardized agar preparation, and by a microbroth test, using dilutions differing by small arithmetic increments. For gentamicin, recently proposed breakpoints of resistance (R) less than or equal to 12 mm and susceptibility (S) greater than or equal to 16 mm produced error rates of 20 and 6.8%, respectively. Limiting the error rate for susceptible interpretations to less than or equal to 2% produced a widening of the intermediate zone to include 67.4% of the isolates tested. For tobramycin, the recently proposed breakpoints of R less than or equal to 12 mm and S greater than or equal to 15 mm were associated with error rates of 66.7 and 1.4%, respectively. Breakpoints of R less than or equal to 12 mm and S greater than or equal to 13 mm were demonstrated to be equally effective when the error rate for susceptible interpretations was limited to less than or equal to 2% by error rate-bound analysis. For amikacin, proposed breakpoints of R less than or equal to 14 mm and S greater than or equal to 17 mm were associated with error rates of 27.3 and 3.2%, respectively. Limiting the error rates for susceptible interpretations to less than or equal to 2% required breakpoints of R less than or equal to 14 mm and S greater than or equal to 18 mm. The ability to establish effective susceptibility breakpoints for tobramycin and amikacin appeared not to be related to the disk agar diffusion test process itself but rather to the high degree of susceptibility of the P. aeruginosa population. These findings severely limit the usefulness of the disk agar diffusion procedure for testing P. aeruginosa versus the aminoglycosides. For this purpose, we recommend dilution tests which employ small arithmetic increment schemes.